Ecuatii logaritmice :
log2 (x + 5/3) = 1 - log2 3x
lg (x + 4) = -2 * lg 1/2-x
lg (5 + x) - lg (1-x) = lg2
sergiutaranu:
Ce e asa dificil?
Răspunsuri la întrebare
Răspuns de
5
a)log2 (x+5/3)=1- log2 3x x+5/3>0 ⇒ x>-5/3
3x>0 ⇒ x>0 ⇒x∈(0,∞)
log2 (x+5/3)=log2 2-log2 3x
log2 (x+5/3)=log2 (2/3x)
x+5/3=2/3x
x-2/3x=-5/3
(3x²-2)=-5x
3x²+5x-2=0
Δ=25+24=49
x₁,₂=(-5+/-7)/6
x₁=(-5+7)/6=2/6=1/3
x₂=(-5-7)/6=(-12)/6=-2
3x>0 ⇒ x>0 ⇒x∈(0,∞)
log2 (x+5/3)=log2 2-log2 3x
log2 (x+5/3)=log2 (2/3x)
x+5/3=2/3x
x-2/3x=-5/3
(3x²-2)=-5x
3x²+5x-2=0
Δ=25+24=49
x₁,₂=(-5+/-7)/6
x₁=(-5+7)/6=2/6=1/3
x₂=(-5-7)/6=(-12)/6=-2
Alte întrebări interesante
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Germana,
9 ani în urmă
Matematică,
9 ani în urmă
Fizică,
10 ani în urmă
Engleza,
10 ani în urmă